Factors associated with recovery from acute optic neuritis in patients with multiple sclerosis - Malik, Muhammad Taimur; Healy, Brian C; Benson, Leslie A; Kivisakk, Pia; Musallam, Alexander; Weiner, Howard L; Chitnis, Tanuja (Neurology, 2014)
To identify clinical and demographic features associated with the severity and recovery from acute optic neuritis (AON) episodes in patients with multiple sclerosis (MS). Adult (n = 253) and pediatric (n = 38) patients whose first symptom was AON were identified from our MS database. Severity measured by loss of visual acuity (mild attack ≤20/40, moderate attack 20/50-20/190, and severe attack ≥20/200) and recovery in visual acuity at 1 year after the attack (complete recovery ≤20/20, fair recovery 20/40, and poor recovery ≥20/50) were recorded. Demographic and clinical features associated with attack severity and recovery were identified using proportional odds logistic regression. For another group of patients, blood samples were available within 6 months of an AON attack. In this group, the impact of vitamin D level on the severity/recovery was also assessed. Men (adjusted odds ratio [OR] = 2.28, p = 0.03) and subjects with severe attacks (adjusted OR = 5.24, p < 0.001) had worse recovery. AON severity was similar between the pediatric and adult subjects, but recovery was significantly better in pediatric subjects in the unadjusted analysis (p = 0.041) and the analysis adjusted for sex (p = 0.029). Season-adjusted vitamin D level was significantly associated with attack severity (OR for 10-U increase in vitamin D level = 0.47; 95% confidence interval: 0.32, 0.68; p < 0.001). Vitamin D level was not associated with recovery from the attack (p = 0.98) in univariate analysis or after accounting for attack severity (p = 0.10). Vitamin D levels affect AON severity, whereas younger age, attack severity, and male sex affect AON recovery. Underlying mechanisms and potential therapeutic targets may identify new measures to mitigate disability accrual in MS.